Inverse coordination chemistry: A novel chemical concept - Haiduc, Ionel; Tiekink, Edward R. T. * (Sunway University Press, 2020)
Inverse Coordination Chemistry: A Novel Chemical Concept presents the fascinating array of inverse coordination complexes, from monoatomic centres to those with organic molecules as centres, in a systematic manner with full-colour illustrative examples. This book is a timely and comprehensive introduction to this largely overlooked field of inverse coordination in inorganic chemistry.